Didactic Situation-Based Model for Using Student Traditional Handcraft Artefacts to Enhance Meaningful STEAM Education in Tanzania - Saimon, Musa; Dana-Picard, Thierry (Noah); Ally, Fatma; Lavicza, Zsolt; Bautista, Guillermo (Journal of Education Culture and Society, 2025)
Aim. The aim of the study was to propose a theoretical model for using students’ traditional handicraft artefacts to enhance meaningful STEAM learning in Tanzania. This study was motivated by lessons we learned in our previous project in which we explored the potential of handicraft artefacts from Tanzania in facilitating STEAM learning and realised the need for the model to support teachers in using these materials in the classroom. Methods. The proposed model is based on the reflection from the Theory of Didactic Situation (TDS) proposed by Brosseau in the 1970s. Results. We have proposed the model with four phases and provided one illustration on how the model can be applied in the classroom. Our illustration from hypothetical lesson plan for Tanzania context shows various possibilities in which the model can enhance meaningful STEAM learning. Conclusions. Despite the reported potential of the model, the use of hypothetical lesson plans makes the proposed model less reliable. Therefore, we will report the experience of applying the model classroom contexts of Tanzania in the next study. Furthermore, we call for research insights on applying the model in other relevant classroom contexts as a way to improve the model where necessary.